Measurement of cross sections of e + e − → K S 0 K S 0 ψ 3686 from s = 4. 682 to 4. 951 GeV - Ablikim, M; Achasov, MN; Adlarson, P; Afedulidis, O; Ai, XC; Aliberti, R; Amoroso, A; An, Q; Bai, Y; Bakina, O; Balossino, I; Ban, Y; et al. (Springer, 2025)
The process e+e−→KS0KS0ψ3686 is studied by analyzing e+e− collision data samples collected at eight center-of-mass energies ranging from 4.682 to 4.951 GeV with the BESIII detector operating at the BEPCII collider, corresponding to an integrated luminosity of 4.1 fb−1. Observation of the e+e−→KS0KS0ψ3686 process is found for the first time with a statistical significance of 6.3σ, and the cross sections at each center-of-mass energy are measured. The ratio of cross sections of e+e−→KS0KS0ψ3686 relative to e+e−→ K+K−ψ(3686) is determined to be σe+e−→KS0KS0ψ3686σe+e−→K+K−ψ3686=0.45±0.25, which is consistent with the prediction based on isospin symmetry. The uncertainty includes both statistical and systematic contributions. Additionally, the KS0ψ3686 invariant mass distribution is found to be consistent with three-body phase space. The significance of a contribution beyond three-body phase space is only 0.8σ.